PIC microcontrollers : an introduction to microelectronics - Bates, Martin, 1952- ([Place of publication not identified] : Newnes, 2012)
PIC Microcontrollers provides a comprehensive and fully illustrated introduction to microelectronic systems principles using the best-selling PIC16 range. Building on the success of previous editions, this third edition will enable readers to understand PIC products and related programming tools, and develop relevant design skills in order to successfully create new projects. Key features include: Initial focus on the 16F84A chip to introduce the basic architecture and programming techniques, progressing to more recently introduced devices, such as the 16F690, and comparison of the whole PIC16 range Use of the standard Microchip development software, MPLAB IDE, as well the interactive ECAD package Proteus VSM Standard Microchip demo hardware, specially designed application boards, in-circuit programming and debugging Basic interfacing, motor drives, temperature control and general control system applications Numerous fully documented code examples which can be downloaded from the companion website The book is aimed principally at students of electronics on advanced vocational and undergraduate courses, as well as home enthusiasts and professional engineers seeking to incorporate microcontrollers into industrial applications. A focus on the 16F84A as the starting point for introducing the basic programming principles and architecture of the PIC, progressing to newer chips in the 16F range, in particular the 16F690, and Microchip starter kits How to use the free Microchip development environment MPLAB IDE, plus Proteus VSM interactive electronic design software, to develop your own applications Numerous fully-documented, working code examples downloadable from the companion website.
Computer Systems -- Microcontroller Operation -- A Simple PIC Application -- PIC Program Development -- Internal Architecture -- Programming Techniques -- Development Systems -- Application Design -- Program Debugging -- Hardware Prototyping -- Motor Applications -- More PIC Microcontrollers -- More PIC Applications -- More Control Systems -- Appendices.
Includes bibliographical references and index.
Keywords: Microcontrollers -- Programming; Programmable controllers; TECHNOLOGY & ENGINEERING -- Automation; Microcontrollers -- Programming; Programmable controllers